Asset pricing theory - Σκιαδάς, Κωστής. (Princeton : Princeton University Press, 2009)
"Asset Pricing Theory is an advanced textbook for doctoral students and researchers that offers a modern introduction to the theoretical and methodological foundations of competitive asset pricing." "Costis Skiadas develops in depth the fundamentals of arbitrage pricing, mean-variance analysis, equilibrium pricing, and optimal consumption/portfolio choice in discrete settings, but with emphasis on geometric and martingale methods that facilitate an effortless transition to the more advanced continuous-time theory." "Asset Pricing Theory is complete with extensive exercises at the end of every chapter and comprehensive mathematical appendixes, making this book a self-contained resource for graduate students and academic researchers, as well as mathematically sophisticated practitioners seeking a deeper understanding of concepts and methods on which practical models are built."--BOOK JACKET.
Single-period analysis. Financial market and arbitrage -- Mean-variance analysis -- Optimality and equilibrium -- Risk aversion -- Discrete dynamics. Dynamic arbitrage pricing -- Dynamic optimality and equilibrium -- Mathematical background. Appendix A: Optimization principles -- Appendix B: Discrete stochastic analysis.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Capital assets pricing model; Finance -- Mathematical models